Single Staged Mastopexy With Autologous Fat Grafting: An Alternative to Augmentation Mastopexy With Implants. (21st November 2019) - Walters, Jules; Bourn, Lynn; Tessler, Oren; Patterson, Charles; Khoobehi, Kamran
Abstract: Background: Improving the ptotic breast with mastopexy and restoring upper pole fullness with augmentation continues to be a challenging issue for plastic surgeons. Autologous fat grating (AFG) for shaping and contouring of implant augmented breasts has shown positive outcomes with few complications. Objectives: The objective of this study was to evaluate our experience with combined mastopexy and fat grafting for women with existing breast ptosis who prefer not to receive prosthetic breast implants but do desire volume enhancement. Methods: A retrospective review of patients undergoing a single staged mastopexy with AFG, from 2006 to 2017, was performed. Inclusion criteria were women with breast ptosis or tuberous breasts desiring improved breast shape and volume. Patients were excluded if they were undergoing implant removal before the procedure. Clinical aesthetic outcomes were assessed by fellow plastic surgeons according to the Telemark Breast Scoring system. Results: A total of 284 breasts, in 140 women, underwent a single staged mastopexy with AFG. The mean amount of fat grafted per breast was 299.4 mL (range, 50-710 mL). There were no surgical site infections, hematomas, or seromas. There were 3 major and 8 minor (0.06%) postoperative breast complications. A total of 13 plastic surgeons, of the 183 invited (7.1%), completed the breast outcomes survey. Regarding each category, there was significant improvement ( P ≤ 0.0001) in upper pole fullness, ptosis, overall aesthetics, and symmetry postoperatively. Conclusions: AFG combined with mastopexy is not associated with significant postoperative complications and results in excellent breast aesthetic outcomes. Level of Evidence: 4: